Assessing the Impact of Audit Quality on Earnings Management Strategies: A Comprehensive Study - Sulieman, Mohammad Tayseer; Rashid, Norfadzilah; Dakhlallh, Mohammad Mustafa (Journal of Ecohumanism, 2024)
The purpose of the current study is to examine whether audit quality is capable to restrict earnings management in a developing country such as Jordan. The fixed effect method was used to study the association between two audit quality (audit fees and audit firm size) and discretionary accruals (AEM) with real activities (REM) as a proxy of earnings management, for the industrial service firms listed on the Amman Stock Exchange (ASE) during the period 2012-2021. Using 740 firm-year observations, the results showed that the audit fees (AFEE) are significantly and positively related to earnings management measured by discretionary accruals (AEM), while the aggregated measure of real earnings management (REM) shows a significant negative association with the audit fees (AFEE). Meanwhile, the result showed that the existence of audit firm size (B4) is a negative and significant effect on earnings management measured by discretionary accruals (AEM) and the aggregated measure of real earnings management (REM). Thus, these findings provide shreds of evidence for all of the regulators, investors, and executives in Jordan into account when designing corporate regulations. Hence, due to the significant impact on public policies, the results should be of interest to the regulators and standard setters.